Importance of Data Analytics in the Supply Chain in Distribution Companies (Revista Cientifica Ingenio Magno, 2024)
This study highlights the importance of data analytics in the management of the supply chain of distribution companies, improving efficiency, visibility and decision making. The methodology includes the collection and analysis of information from sources such as Google Scholar, Scopus and ScienceDirect, focusing on publications from the last 5 years. Of fifty initial articles, twenty-five were selected for the development of the document, organized in an Excel matrix. The results show that data analytics is essential for distribution companies, allowing them to make informed decisions, identify market patterns and quickly adapt to changes in demand and supply. Its implementation improves operational efficiency and the ability to respond to logistical and operational challenges, especially in small and medium-sized companies. In conclusion, data analytics is positioned as an invaluable strategic resource in supply chain management, providing a significant competitive advantage in the pursuit of operational excellence and business success. This study is distinguished by its focus on the systematic review of data analytics in distribution companies, providing updated knowledge about its impact on operational efficiency and business competitiveness.
Keywords: data analytics; supply chain; distribution companies; logistics management